HIV and COVID-19: A Tale of Two Pandemics - Kurdekar, Aditya; Verma, Shruti; Venkataramaniah, Kamisetti (Current HIV Research, 2022)
In the last 5 decades, we have witnessed two major pandemics, AIDS caused by the Human Immunodeficiency Virus (HIV) and the CoronaVirus Disease-19 (COVID-19) caused by the Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2). The emergence of COVID-19 has raised many concerns for researchers, doctors, patients, and other institutions associated with HIV. A lot of debate has persisted on clinical outcomes, the use of antiretrovirals, and vaccines on HIV patients infected with COVID-19. This note attempts to present different aspects of HIV and SARS-CoV-2 across themes like SARS-CoV-2 coinfections in people living with HIV, the psychological impact, treatments, vaccination, etc. We highlight how learnings from the COVID-19 pandemic can help us in tackling the HIV pandemic.
Keywords: antiretrovirals